How is disability portrayed through Welsh universities' Disability Service web pages?: A Critical Disability Studies perspective. Issue 1 (1st March 2021) - Pickard, Beth
Abstract: This article explores the portrayal of disability through the Disability Service web pages of Welsh universities in order to understand their potential impression on disabled applicants. The method of Qualitative Content Analysis enables consideration of multiple dimensions including use of language, terminology and photography, as well as discussion of academic, cultural, social and logistical aspects of student life. The development of a primarily concept-driven coding frame enables consideration of the absence of certain criteria as well as the frequency and prominence of others. The ensuing discussion considers, from a Critical Disability Studies perspective, the sector's portrayal of the construct of disability. This article proposes a call to action to challenge deficit-based interpretations of disability and advocates an affirmative stance towards disability in higher education policy and practice.